Stretchable and sensitive sensor based on carbon nanotubes/polymer composite with serpentine shapes via molding technique. Issue 13 (2nd September 2019) - Fu, Xiang; Al-Jumaily, Ahmed M.; Ramos, Maximiano; Meshkinzar, Ata; Huang, Xiyong
Abstract: With the rapid development of wearable devices in recent years, stretchable strain sensors based on electrically conductive composites have attracted a great deal of attention owing to their good stretchability and piezoresistivity. However, due to the intrinsic restriction of these types of composites, the conventional stretchable strain sensors cannot do well in all aspect of sensing performance. A stretchable strain sensor based on carbon nanotubes/poly(dimethylsiloxane) composite with the serpentine shape was devised and fabricated. The sensor was readily manufactured through a molding technique. Not only can this sensor distinguish tension strain from transverse or longitudinal direction, but also exhibits good linearity of response to tensile strain. In terms of sensitivity, hysteresis and response time, the stretchable strain sensor showed significant performance. The sensing performance of this proposed stretchable sensor has been demonstrated to be good in this work and it also shows a good prospect for utilization in multifunctional wearable devices.